Gender perspective in the news of rape on Harian Haluan - Hendrika Era Farida; Novia Juita; Ngusman Abdul Manaf (Fakultas Ilmu Pendidikan UNP)
Coverage on certain mass media allegedly marginalizes women victims of rape. The purpose of this study was to to describe the gender perspective in the news of rape on the Harian Haluan. This writing analyzes reports of rape in the mass media using the method of critical discourse analysis model Sara Mills. The results showed (1) the position of women in the news of rape on the dominant Harian Haluan as the object of telling and (2) the gender ideology in the news of rape on Harian Haluan is patriarchy ideology. Most of the news of rape contains the assumption that men have power over women so women tend to be inferior and subordinated. Furthermore, the alignment of journalists in the news of rape on Harian Haluan, it was concluded that journalists tend to side with the perpetrators of rape.